Propagation Dynamics of Finite-Energy Airy Pulses in a Cubic–Quintic Competing Nonlinear Fiber - Xin Yan; Xingfang Zhang; Fengshou Liu; Zhenghua Li; Liang Xu; Yuanping Li (IEEE Photonics Journal, 2017)
We numerically simulated dynamic propagation of in-phase and out-of-phase finite-energy Airy pulses in anomalous regions of optical fibers and analyzed the effects of cubic-quintic (CQ) competing nonlinearity and separation parameter on evolution properties. Numerical results showed entirely different effects of quintic nonlinearity on in-phase and out-of-phase Airy pulses that vary with different separation parameters. For in-phase Airy pulses, a central quasi-soliton pulse is shed from all finite-energy Airy pulses when separation parameter is certain. CQ competing nonlinearity exhibits profound effects on propagation dynamics of soliton pulses. However, for out-of-phase Airy pulses, two quasi-soliton pulses and more dispersion wave pulses are symmetrically shed from the main lobe of out-of-phase Airy pulses. CQ competing nonlinearity slightly impacts evolution of out-of-phase Airy pulses depending on peak intensity, which varies with propagation distance and unlike in cases of in-phase Airy pulses.